The Effect of Self-Regulation on Burnout in Teachers at Medan Mulia Schools - Koesuma, Hendryo; Hartini, Sri; Carolin, Vivian; Anggriani, Putri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Burnout in teachers is a problem that can affect the effectiveness of education. This study aims to analyze the relationship between self-regulation and Burnout in teachers at Medan Mulia School. The research method used is a quantitative approach with a correlational design. The research sample amounted to 119 teachers who were selected using a random sampling technique. Data was collected through Burnout and self-regulation scales, which were tested for validity and Reliability before use. The Pearson Product Moment analysis showed a significant negative relationship between self-regulation and Burnout (r = -0.514, p < 0.001). Self-regulation contributes 26.5% to burnout rates, while other factors influence the rest. These findings confirm that improving self-regulation can effectively reduce teacher burnout, thereby supporting optimal teaching quality.